2021
DOI: 10.1681/asn.2021020267
|View full text |Cite
|
Sign up to set email alerts
|

A Higher Foci Density of Interstitial Fibrosis and Tubular Atrophy Predicts Progressive CKD after a Radical Nephrectomy for Tumor

Abstract: Background Chronic tubulointerstitial injury on kidney biopsy is usually quantified by the percentage of cortex with interstitial fibrosis/tubular atrophy (IF/TA). Whether other patterns of IF/TA or inflammation in the tubulointerstitium have prognostic importance beyond percentage IF/TA is unclear. Methods We obtained, stained, and digitally scanned full cortical thickness wedge sections of renal parenchyma from patients who underwent a radical nephrectomy for tumor in 2000 to 2015 and morphometrically analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
46
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(47 citation statements)
references
References 45 publications
(111 reference statements)
1
46
0
Order By: Relevance
“…While IF/TA appears to be less prominent when due to nephron loss from aging rather than from CKD, the pattern of IF/TA with aging is also informative. Analysis of large wedges of unaffected kidney tissue from patients undergoing radical nephrectomy for tumors reveals that older patients have a more scattered pattern of IF/TA at the same %IF/TA as younger patients (6). This suggests: ( 1 ) IF/TA foci atrophy into smaller IF/TA foci with contraction of the cortex, which increases their density; and ( 2 ) this atrophy helps explain the minimal extent of %IF/TA in older individuals despite significant loss of nephrons.…”
mentioning
confidence: 99%
“…While IF/TA appears to be less prominent when due to nephron loss from aging rather than from CKD, the pattern of IF/TA with aging is also informative. Analysis of large wedges of unaffected kidney tissue from patients undergoing radical nephrectomy for tumors reveals that older patients have a more scattered pattern of IF/TA at the same %IF/TA as younger patients (6). This suggests: ( 1 ) IF/TA foci atrophy into smaller IF/TA foci with contraction of the cortex, which increases their density; and ( 2 ) this atrophy helps explain the minimal extent of %IF/TA in older individuals despite significant loss of nephrons.…”
mentioning
confidence: 99%
“…One study found 21% of native kidney biopsy patients with >50% IFTA had not progressed to ESKD at 5 years after their biopsy. Among radical nephrectomy patients, those with smaller more scattered IFTA foci were older, had smaller cortical volumes on imaging, and were more likely to have progressive CKD than those with the same %IFTA but larger and fewer IFTA foci 18 . As seen in nephrectomy patients, 18 IFTA foci density also had an inverted U-shaped association with %IFTA in native kidney biopsy patients.…”
Section: Discussionmentioning
confidence: 83%
“…To calculate %IFTA, the total areas of all IFTA foci were divided by the total area of cortex 8 . The IFTA foci density was calculated by dividing the count of distinct IFTA foci by the traced cortical area (number of IFTA foci per square millimeter) 18 . The %luminal stenosis (morphometric measure of arteriosclerosis) was determined from the area of intima divided by the area of intima and lumen 27 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some of them have an underlying chronic disease, which will cause worsening kidney function over time [ 5 ]. In addition, pathology examination of radical nephrectomy always shows some kidney disease in the “no-tumor part” [ 6 ], which may be associated with CKD after RN [ 7 ]. Therefore, the probability of CKD after radical nephrectomy is often higher than expected.…”
Section: Discussionmentioning
confidence: 99%